EFFECT OF Chaetomorpha sp. EXTRACT ON THE HEMATOLOGY OF TILAPIA (Oreochromis niloticus) INFECTED WITH Aeromonas hydrophila - M. Riswan; Sri Wahyuni; Ronal Kurniawan; Hayatun Nufus; Asri Mursawal (Asian Journal of Aquatic Sciences, 2025)
Chaetomorpha sp. is a green macroalgae that contains various bioactive compounds with antibacterial and anti-inflammatory activities, as well as the potential to improve the physiological health of fish. This research investigates how incorporating Chaetomorpha sp. extract into the diet influences the hematological parameters of Tilapia (Oreochromis niloticus) challenged with Aeromonas hydrophila. The study used a completely randomized design (CRD) with four levels of extract supplementation (0, 25, 50, and 75 mL/kg of feed), with each treatment replicated three times. The hematological parameters analyzed included total erythrocytes, hematocrit, hemoglobin, and blood glucose. The findings indicated that adding Chaetomorpha sp. extract to the diet significantly (p<0.05) improved all hematological indicators relative to the control, with 50 mL/kg of feed as the most effective dosage. The highest erythrocyte count 1.89 x106 cells/mm3, hematocrit value 35.67%, hemoglobin concentration 6.87 g/dL and  blood glucose level 90 mg/dL were observed in fish fed 50 mL/kg extract. This increase in hematological values indicates improved oxygen transport capacity, physiological condition, and metabolic response in fish. Bioactive constituents, including sulfated polysaccharides and flavonoids, are believed to enhance the hematological condition of fish. These findings confirm the potential of Chaetomorpha sp. as a natural supplement to support Tilapia health in sustainable aquaculture systems.